2012
DOI: 10.1108/03684921211243400
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a cybernetic epistemology: output‐side attention directing systems

Abstract: Purpose -The purpose of the paper is to analyze cybernetic necessities of output-side attention directing systems, i.e. how systems can decide to act towards one of various inputs. Design/methodology/approach -Complex pattern recognition and sequence learning systems may recognize more than one pattern and deliver more than one output at a point in time. Therefore, they require an output-side attention directing system to decide to act towards just one pattern. The necessary cybernetic structures of such syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…(3) When investigating learning systems that can learn new patterns by themselves, we found that they can develop goal-orientated behavior towards new patterns only after a trial and error process (Nechansky, 2012). And in that process they have to determine, which degree of goal-approximation they achieved with the actions they tried.…”
Section: The Problem Of Controlling Attentionmentioning
confidence: 99%
“…(3) When investigating learning systems that can learn new patterns by themselves, we found that they can develop goal-orientated behavior towards new patterns only after a trial and error process (Nechansky, 2012). And in that process they have to determine, which degree of goal-approximation they achieved with the actions they tried.…”
Section: The Problem Of Controlling Attentionmentioning
confidence: 99%
“…Now such "knowledge" can be acquired in principle with the sequence learning process we discussed elsewhere (Nechansky, 2012a). But the decisive prerequisite, that longer sequences are possible at all, is the ability to connect known patterns to sequences.…”
Section: From Elementary To Complex Anticipationmentioning
confidence: 99%
“…As already mentioned we will consider here just temporal patterns connected via the "associative" way (Nechansky, 2012a).…”
Section: Necessary Structures For a Subsystem For Complex Anticipationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can only start with the action previously applied towards that pattern in the feedback mode, from which it derived the current evaluation of that pattern (Nechansky, 2012a).…”
Section: Learning To Act Successfully Towards Anticipated Patternsmentioning
confidence: 99%